Oryza-Specific Orphan Protein Triggers Enhanced Resistance to Xanthomonas oryzae pv. oryzae in Rice - Moon, Hyeran; Jeong, A-Ram; Kwon, Oh-Kyu; Park, Chang-Jin (Frontiers in Plant Science, 2022)
All genomes carry lineage-specific orphan genes lacking homology in their closely related species. Identification and functional study of the orphan genes is fundamentally important for understanding lineage-specific adaptations including acquirement of resistance to pathogens. However, most orphan genes are of unknown function due to the difficulties in studying them using helpful comparative genomics. Here, we present a defense-related Oryza-specific orphan gene, Xio1, specifically induced by the bacterial pathogen Xanthomonas oryzae pv. oryzae (Xoo) in an immune receptor XA21-dependent manner. Salicylic acid (SA) and ethephon (ET) also induced its expression, but methyl jasmonic acid (MeJA) reduced its basal expression. C-terminal green fluorescent protein (GFP) tagged Xio1 (Xio1-GFP) was visualized in the nucleus and the cytosol after polyethylene glycol (PEG)-mediated transformation in rice protoplasts and Agrobacterium-mediated infiltration in tobacco leaves. Transgenic rice plants overexpressing Xio1-GFP showed significantly enhanced resistance to Xoo with reduced lesion lengths and bacterial growth, in company with constitutive expression of defense-related genes. However, all of the transgenic plants displayed severe growth retardation and premature death. Reactive oxygen species (ROS) was significantly produced in rice protoplasts constitutively expressing Xio1-GFP. Overexpression of Xio1-GFP in non-Oryza plant species, Arabidopsis thaliana, failed to induce growth retardation and enhanced resistance to Pseudomonas syringae pv. tomato (Pst) DC3000. Our results suggest that the defense-related orphan gene Xio1 plays an important role in distinctive mechanisms evolved within the Oryza and provides a new source of Oryza-specific genes for crop-breeding programs.